Effects of applying locust frass on the soil properties and microbial community in a peach orchard - Ji'ang Nie; Hao Chen; Yongdong Wang; Dapeng Zhang; Yao Wang; Zheng Gao; Ningxin Wang (Microbiology Spectrum)
ABSTRACT Insect frass, a by-product of insect cultivation, represents an emergent category of agricultural waste. How to develop and make full use of this waste is a major issue to be addressed. In this study, the locust (Locusta migratoria) frass was used as an organic fertilizer in a peach orchard, and its effects on soil were investigated, including physicochemical properties and microbial community over three consecutive years. Compared to chemical fertilizer (CF), the application of locust frass (LF) enhanced the alpha diversity and network complexity of the soil microbial community. Furthermore, locust frass application led to an enrichment of functional microbial groups associated with the nitrogen cycle and enhanced the contents of nitrogen in the soil. Bacillus was identified as keystone microbes that discriminated between locust frass and chemical fertilizer treatments, and promoted the growth of Chinese cabbage (Brassica campestris L.) in pot experiments. The abundance of Bacillus diminished with successive applications of chemical fertilizers, whereas its prevalence remained consistent in the soil with application of locust frass. Importantly, locust frass application led to an enrichment of functional microbial groups associated with the nitrogen cycle and enhanced the contents of nitrogen in the soil. Structural equation modeling (SEM) suggests that nitrite respiration after locust frass application had a negative effect on soil total nitrogen content and that total nitrogen affected the entire taxa by affecting the rare taxa. Our results provided a theoretical basis for the application of locust frass as organic fertilizer.IMPORTANCEInsect frass is a new type of organic fertilizer. The effects of some insect frass on soil have been investigated. However, the effect of locust frass (LF) (a by-product of the rearing process of this major edible insect) as an organic fertilizer is not well known. This study investigates the effects of locust frass on soil properties and the microbial community, providing valuable guide on its use as an organic fertilizer in agricultural production.